2015
DOI: 10.1111/ddg.12687
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective data collection of psoriasis treatment with fumaric acid esters in children and adolescents in Germany (KIDS FUTURE study)

Abstract: SummaryBackground: Given that there is no standard systemic treatment for children and adolescents with plaque psoriasis, this non-interventional, multicenter, retrospective study collected data on the efficacy and safety of long-term treatment with fumaric acid esters (FAEs) in this particular patient group. Patients and methods: In patients younger than 18 years of age at the start of FAE treatment, data on efficacy and safety was retrospectively collected for at least 36 months. Results: Data from 127 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 31 publications
3
18
0
5
Order By: Relevance
“…A previously published retrospective study (‘FUTURE’ study) of 984 psoriasis patients with a mean duration of 44 months of continuous FAE monotherapy reported greater improvement, as assessed with the dynamic PGA: 67% of patients were documented as improved or clear after 0.5 years, 78% after 2 years and 82% after 3 years of FAE therapy. However, the following parameters differed, preventing direct comparison: (i) different PGA scores were used and (ii) patients who stopped FAE monotherapy within the first 2 years because of lack of efficacy or insufficient tolerability were not recorded in the FUTURE study . In our study, all patients were included in data analysis, irrespective of treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previously published retrospective study (‘FUTURE’ study) of 984 psoriasis patients with a mean duration of 44 months of continuous FAE monotherapy reported greater improvement, as assessed with the dynamic PGA: 67% of patients were documented as improved or clear after 0.5 years, 78% after 2 years and 82% after 3 years of FAE therapy. However, the following parameters differed, preventing direct comparison: (i) different PGA scores were used and (ii) patients who stopped FAE monotherapy within the first 2 years because of lack of efficacy or insufficient tolerability were not recorded in the FUTURE study . In our study, all patients were included in data analysis, irrespective of treatment discontinuation.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge several potential limitations of this observational study. First, the study's retrospective design may have resulted in recall bias . Incomplete data recording in the hospital digital database and patients lost to follow‐up resulted in missing data, particularly on continuation of FAE therapy regimens.…”
Section: Limitationsmentioning
confidence: 99%
“…Although the use of DMF in the paediatric population is off‐label, there are numerous case reports, case series and unpublished clinical experience to suggest that FAEs may be an effective treatment option for children and adolescents if a systemic therapy is indicated . A German multicentre, retrospective study on the efficacy and safety of long‐term use of FAEs in children and adolescents showed that FAEs were often used successfully in clinical practice as off‐label therapy . Trials of DMF in paediatric populations and for more moderate disease are ideally needed.…”
Section: Patient Profile and Selectionmentioning
confidence: 99%
“…Zunächst war ein Fertigarzneimittel mit einem Wirkstoffgemisch aus Dimethylfumarat und Salzen von Ethylhydrogenfumarat (Fumaderm ® ) in Deutschland verfügbar, seit 2017 existiert zudem eine Zulassung der europäischen Arzneimittelagentur (EMA) für ein Dimethylfumarat‐Monopräparat (Skilarence ® ). Über die Anwendung von Fumaderm ® bei Kindern und Jugendlichen mit Psoriasis vulgaris wurden mehrere Fallberichte, Fallserien und retrospektive Datenerhebungen publiziert . Auch für die Anwendung eines Dimethylfumarat‐Monopräparates existiert eine retrospektive Datenerhebung, allerdings in der Indikation multiple Sklerose .…”
Section: Therapieunclassified